EVALUATIVE PRACTICES IN THE DIGITAL AGE IN THE ALGERIAN UNIVERSITY CONTEXT - Naoual AOUALI; Hamida DOULATE SEROURI (Universitaria Publishing House, Craiova, 2023)
This article aims to show the circumstances of the evaluation carried out remotely at the Algerian university during the period of confinement and even after the Covid-19 pandemic. The objective is to specify the criteria for a credible distance evaluation which judges the effectiveness of the teaching provided. To achieve this, we conducted a semi-structured interview with teachers from different Algerian universities and different disciplines. We adopted the quantitative/qualitative approach. Likewise, we focused on the characteristics (material and intellectual) drawn from Clark's work to be able to qualify the evaluation carried out remotely. We also developed the Stufflebeam CIPP model for analyzing the evaluation process. The results of our study show that teachers refer to different types of remote assessment. They can assess students through quiz-style exercises. They also involve students in online discussion forums. However, a quality remote assessment is achieved through the availability of technological means and coherent and structured work by the teacher.